Paternal preconception phthalate exposure alters sperm methylome and embryonic programming. (October 2021) - Oluwayiose, Oladele A.; Marcho, Chelsea; Wu, Haotian; Houle, Emily; Krawetz, Stephen A.; Suvorov, Alexander; Mager, Jesse; Richard Pilsner, J.
Highlights: Male preconception DEHP exposure in mice modified DNA methylomes in F0 sperm and F1 embryo. Male preconception DEHP exposure altered F1 embryonic transcriptome at developmental genes. Spermatogenesis is a sensitive window that may alter F1 development. Abstract: Preconception environmental conditions have been demonstrated to shape sperm epigenetics and subsequently offspring health and development. Our previous findings in humans showed that urinary anti-androgenic phthalate metabolites in males were associated with altered sperm methylation and blastocyst-stage embryo development. To corroborate this, we examined the effect of preconception exposure to di(2-ethylhexyl) phthalate (DEHP) on genome-wide DNA methylation and gene expression profiles in mice. Eight-week old C57BL/6J male mice were exposed to either a vehicle control, low, or high dose of DEHP (2.5 and 25 mg/kg/weight, respectively) for 67 days (~2 spermatogenic cycles) and were subsequently mated with unexposed females. Reduced representation bisulfite sequencing (RRBS) of epididymal sperm was performed and gastrulation stage embryos were collected for RRBS and transcriptome analyses in both embryonic and extra-embryonic lineages. Male preconception DEHP exposure resulted in 704 differentially methylated regions (DMRs; q-value < 0.05; ≥10% methylation change) in sperm, 1, 716 DMRs in embryonic, and 3, 181 DMRs in extra-embryonic tissue. Of these, 29 DMRs overlapped between sperm and F1 tissues, half of which showed concordant methylation changes between F0 and F1 generations. F1 transcriptomes at E7.5 were also altered by male preconception DEHP exposure including developmental gene families such as Hox, Gata, and Sox . Additionally, gene ontology analyses of DMRs and differentially expressed genes showed enrichment of multiple developmental processes including embryonic development, pattern specification and morphogenesis. These data indicate that spermatogenesis in adult may represent a sensitive window in which exposure to DEHP alters the sperm methylome as well as DNA methylation and gene expression in the developing embryo.